La diversidad lingüística de Costa Rica: las lenguas indígenas - Constenla Umaña, Adolfo (2013)
This paper as requested by the organizers of the First Week of Linguistic Diversity, deals with the origin of the Amerindian languages of Costa Rica, which were already in its territory at the pre-Columbian time, which are found currently , and what is their state, and, finally, what kind of elements were borrowed from them by Spanish, the dominant language of the country.